Surface integrity of honing - Szabo, O. (НТУ "ХПИ", 2011)
Component surface quality greatly influences the working properties. Type of machining, the applied tools and technological characteristics have an effect on the roughness and microtopography of the machined surface and on their tribological properties. The article introduces important tribological and surface roughness characteristics of honed or microfinished surfaces and suggests methods for their determination respectively.

Составляющие поверхностного качества значительно влияют на эксплуатационные свойства. Тип механической обработки, используемых инструментов и технологические особенности оказывают влияние шероховатость и микротопографию поверхности после механической обработки и на ее трибологические свойства. В статье предложены важные трибологические и поверхностные характеристики точности обработанных поверхностей при хонинговании, а также методы для их определения.
Шероховатость поверхности при хонинговании
Keywords: working properties; technological characteristics; tribological properties; stick-slip effect; механическая обработка; хонингование